8 - Sénégal-Maroc : usages et mésusages de la circulation des ressources symboliques et religieuses entre deux pays « frères » - Seck, Abdourahmane (Africa Development, 2021)
This article focuses on the relationship between Senegal and Morocco and questions the construction and circulation of symbolic resources mobilized by the actors (states, governments, migrants, people, etc.) to promote their respective projects. The article also provides an overview of research opportunities that give precedence to non-institutional players in the relationship between these two spaces.